Analysing the impact of macroeconomic variables on non-performing loans in Nepalese banks - Pandey, Baikuntha (Butwal Campus Journal, 2024)
Nepal’s financial system is largely bank-centric, with 18 private and 3 state-owned commercial banks as of 2023. Non-performing loans (NPLs) directly impact financial stability and the broader economy, making it essential to understand how macroeconomic indicators affect these loans. This study analyzes trends in NPL ratios between state-owned and privately owned commercial banks in Nepal, focusing on the influence of real GDP growth, the Nepal Rastra Bank (NRB) policy rate, and inflation on NPL levels. Using an explanatory research design, the study draws on secondary data from the Nepal Rastra Bank, the National Statistics Office, and the IMF, covering quarterly data from 2007/08 Q2 to 2022/23 Q1. The dependent variable, NPLs, is analyzed against independent variables—real GDP growth, NRB policy rate, and inflation. Adjustments are made to the CPI data, rebased to 2010/11, with seasonal adjustments applied using X12 from the US Bureau of Statistics. An ARDL regression model, combined with unit root testing, is used to measure the macroeconomic impacts on NPLs, with a robustness check involving data on private bank NPLs. The findings reveal that state-owned banks maintain higher NPL ratios than private banks. Moreover, inflation has been shown to have a significant negative effect on NPLs, while the NRB policy rate has had a considerable positive impact. The findings offer actionable insights for regulators, commercial banks, and policymakers to develop tailored strategies for mitigating NPL risks, contributing to the overall financial stability and economic resilience of Nepal.